ANALYSIS OF THE APPLICATION OF NON-TARIFF MEASURES IN THE EURASIAN ECONOMIC UNION (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
Тo protect the interests of the population, including domestic producers, the EAEU legal framework provides for the use of trade regulation instruments. The Treaty on the Union contains provisions on the implementation by EAEU countries of non-tariff measures both in the domestic market and with respect to third countries, in accordance with national legislation.However, the Treaty on the Union does not define the concept of non-tariff measures in the domestic market nor the procedure for their application, which leads to legal conflicts, differing interpretations, and inconsistent enforcement of the relevant Union law. The purpose of this study is to analyze the application of non-tariff measures in the Eurasian Economic Union, identify problematic issues, and develop recommendations for their resolution.
Keywords: non-tariff regulation, mutual trade, foreign trade, restrictions.